Teaching the reading of heritage books using the selective method at the Darul Ulum Banyuanyar Pemekasan - Ma'sud, Ahmad Tarajjil; Muchit, Romli A.; Jazilah, Ela (Al-Ahruf (Journal for Arabic and Linguistics Education), 2023)
This study aims to explain the learning process of Islamic heritage books with this eclectic method which is applied at the Darul Ulum Banyuanyar Islamic Boarding School Pamekasan is planning implementing and evaluating in process is carried out. This research method uses a descriptive qualitative approach, with data collection methods in the form of observation, interviews and observations. Then, the collected data were analyzed using data analysis techniques in the form of data collection, data reduction, data display, and conclusion/verification. The validity of this research data uses the technique of triangulation method and member check. The results of this study are: (a) Learning planning starting with carrying out tests, determining mentors, conducting training for mentors, carrying out tests for mentors, and forming groups according to initial test results. And the media used is, question and answer guidebooks, whiteboards, markers, erasers, projectors, sound systems, and microphones, (b) The implementation is carried out in a week of 5 days, giving value to sentences read and translated using Madurese language, and (c) Evaluation of learning is an oral test which is carried out every time you complete 10 material numbers. المراجع أبو جعفر محمد ابن جرير الطبري. جامع البيان عن تأويل آي القرآن. بيروت لبنان: دار الفكر أحسن. "استخدام طريقة القراءة في ترقية مهارة قراءة كتب التراث (بحث تجريبي في المدرسة التأهيلية للمعهد سلفية شافعية سكرجو سيتوبندو جاوى الشرقية)". رسالة الماجستير، جامعة مولانا مالك إبراهيم الإسلامية الحكومية بمالانج، 2011 أحمد مختار عمر. معجم اللغة العربية المعاصرة. القاهرة: عالم الكتب، 2008 حسين محمد سليمان. التراث العربي الإسلامي، دراسة تاريخية ومقارنة. القاهرة: دار الشعب، 1987 طارق محمد. تعريف التعليم. موقع موضوع، تم الوصول إليه في التاريخ 19 من ديسمبر 2022، الرابط : https://mawdoo3.com/تعريف_التعليم غفران حنبلي الهجوم. مجلة عربية علمية للبرنامج الخاص لتعليم اللغة العربية. الجامعة الإسلامية الحكومية مالانج، 2006 لويس معلوف. المنجد في اللغة والأعلام.بيروت: دار المشرق، 1986 محمود على سمان. التوجيه في تدريس اللغة العربية (كتاب المعلم والموجه والباحث في طرق تدريس اللغة العربية). دار المعارف ، Ahmadi, dan Aulia Mustika Ilmiani. Metodologi Pembelajaran Bahasa Arab Konvensional hingga Era Digital. Yogyakarta: RUAS MEDIA, 2020 Ahsanuddin, "Tahapan Pembelajaran", Situs YPTK, diakses pada tanggal 19 Desember 2022, https://terbitkanbukugratis.id/ahsanuddin/05/2021/tahapan -pembelajaran/ Anshori, Ahmad Muhtadi. Pengajaran Bahasa Arab Media dan Metode-Metodenya,.Yogyakarta: Penerbit TERAS, 2009 Ardiansyah, Ade Arip Ardiansyah. “Implementasi Metode Ibtidai dalam Pembelajaran Kitab Kuning di Pondok Pesantren Hidayatul Mubtadiien Majalengka”. Jurnal Al-ittijah, Vol. 12 No. 1 (Juni 2020) Arif, Armai. Pengantar dan Metodologi Pendidikan Islam. Jakarta: Ciputat Pers, 2002 Asyrofi, Syamsuddin, dan Toni Pransiska. Desain Pembelajaran Bahasa Arab Model, Strategi, dan Permainan Edukatif. Yogyakarta: CV Pustaka Ilmu, 2019 Azizah, Euis Maylati. “Implementasi Metode Sorogan dalam Pembelajaran Kitab Kuning di Pesantren Daar El-Hikam”. Skripsi, UIN Syarif Hidayatullah Jakarta, 2021 Depag RI. Pondok Pesantren dan Madrasah Diniyah Pertumbuhan dan Perkembangannya. Jakarta: Direktorat Jenderal Kelembagaan Agama Islam, 2003 Dhofier, Zamakhsyari. Tradisi Pesantren Studi Tentang Pandangan Hidup Kyai. Jakarta: LP2ES, 1995 DJmarah, Syaiful Bahri dan Aswan Zain.  Strategi Belajar Mengajar. Jakarta : Rineka Cipta, 2014 Hermawan, Acep. Metodologi Pembelajaran Bahasa Arab. Bandung: PT Remaja Rosdakarya, 2011 Muzaky, Choirul Mala dan Nurhafid Ishari.  “Implementasi Metode Al-Miftah Lil Ulum dalam Pembelajaran kitab kuning di Pondok Pesantren Sidogiri Pasuruan”. Tarbiyatuna: Jurnal Pendidikan Islam. Vol. 13 No. 1, (Februari 2020) Nata, Abuddin. Perspektif Islam tentang Strategi Pembelajaran. Jakarta: Kencana Prenada Media Groum, 2009 Rahmawati, Rani. “Syawir Pesantren sebagai Metode Pembelajaran Kitab Kuning di Pondok Pesantren Manbaul Hikam Desa Putat, Kecamatan Tanggulangin, Kabupaten Sidoarjo-Jawa Timur”. AntroUnairdotNet, Vol, V No. 2 (Juli 2016) Setneg RI, UU No. 20 Tahun 2003, Pasal 13 Ayat 1 Setneg RI, UU No. 18 Tahun 2009, Pasal 1 Ayat 3 Sarkawi. “Sistem Pembelajaran Pondok Cilik Maktab Nubdzatul Bayan Mambaul Ulum Bata-Bata Pamekasan”. Jurnal Tadris. Vol 7 No. 2 (Desember 2012) Sugiyono. Metode Penelitian Kuantitatif, Kualitatif dan R&D. Bandung: Alfabeta, 2019 Tim Redaksi. "Selamat Tinggal Kitab Kuning". Majalah Sidogiri Media.  Edisi 113 Jumadats Tsani 1437. Pasuruan: Pondok Pesantren Sidogiri, 2016 Zaenuddin, Radliyah. Metodologi dan Strategi Alternatif Pembelajaran Bahasa Arab. Yogyakarta: Pustaka Rihlah Group, 2005